Nursing in the Critical Care Unit in a Caribbean Island - Jervy Pagmanoja, Bernardino (Universiti Malaysia Sarawak (UNIMAS), 2021)
Nursing in the Critical Care Unit (CCU) in the Caribbean, like many other countries in the world, is faced with varying issues, and challenges related to its multifaceted and ever-evolving complex phenomenon as this area is becoming more intense, demanding and complicated. Critical Care Nurses (CCN) have to confront nursing situations marked by many intricacies, vulnerabilities, and uncertainties. While there exists an increasing body of knowledge relative to the practice of nursing in CCU, there is, however, a lack of literature or research elucidating the phenomenon of nursing in CCUs within the Caribbean context. Therefore, this qualitative research study aims to explore the perceptions and experiences of nurses nursing in the CCU setting within the Caribbean. A generic qualitative approach (exploratory-descriptive qualitative) was adopted. Data were collected through semi-structured, in-depth interviews with 13 participants who had been purposefully selected. Data were analysed using rigorous thematic analysis. The framework of Integral Theory by Ken Wilber underpinned the study and provided guidance in the interpretation of the findings. Seven major themes emerged: dynamic and high complexity unit, heavy workload of CCNs, difficult encounter and traumatic experiences, multiculturalism in the workplace, lack of or inadequate material and human resources, undermining and undervaluing of the nursing workforce, and poor organisational climate. Based on the study findings, a framework guideline of support for CCNs was developed that will aid in promoting their welfare and improve the work environment as well as the organisational climate. This study contributes substantive empirical evidence on nurses’ experiences of nursing within the CCU and thus, broadening the breadth of existing literature.